The Influence of Promotion, Service Quality, Brand Image On Indomaret Customer Satisfaction and Loyalty - Yunita, Fina; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2025)
The supermarket sector in Indonesia has shown significant growth over the past few years and is predicted to continue to grow in the future. The purpose of this study was to determine how promotion, service quality, and brand image impact customer satisfaction and customer loyalty, especially Indomaret customers in west Jakarta Indonesia. This study involved the use of quantitative techniques. The population to be studied was Indomaret customers in west Jakarta Indonesia in year 2024 to 2025. Furthermore, for sampling, a nonprobability sampling method with a purposive sampling technique was used. The research sample was 130 people. Smart PLS software was used to perform data analysis with the Structural Partial Least Square Equation Model (SEM-PLS). The results of this study indicated that promotion, service quality, and brand image have an impact on customer satisfaction. In addition, service quality and brand image had a positive impact on customer loyalty. The level of customer satisfaction positively influences customer loyalty. This study was expected to help Indomaret to improve customer satisfaction and customer loyalty. Furthermore, this study can serve as a reference for future research on promotion, service quality, brand image, customer satisfaction, and customer loyalty.